(untitled) (World Bulletin of Social Sciences, 2023)
The current paper is dedicated to the current state of problems with the primary school English curriculum in Uzbekistan. It works out a set of recommendations to revise the primary school English curriculum in Uzbekistan, along with a suggested curriculum plan. The suggested curriculum plan is aligned with CEFR goals. To stimulate a vivid imagination of the proposed curriculum, an example syllabus is also provided, along with a wide selection of assessments. The article estimates the future of education in relation to the recommendations of UNICEF regarding how to realize quality education